Empowering Human Resources Management in Technology to Improve Leadership Function in Business Practice: Systematic Review - SATRIADI,; RIZKI, MUHAMMAD; SAPUTRA, EKA KURNIA (The journal of contemporary issues in business and government, 2021)
This study identifies scientific findings of the relationship between HR empowerment and technology skills to empower leadership skills in functional business areas. Scientists' advice shows a close relationship between HR governance and technological skills and the empowerment of leadership roles in the business world. For that, we reviewed dozens of international publications, and we specialized in around 50 preliminary formulation papers and problems and ten leading publications as important findings data. We chose data analysis utilizing the coding and in-depth interpretation for valid and reliable findings and answered the research questions. We are looking for data sources electronically on Google scholar, Publication ERIC, and Microsoft academic data sources from 2015 to 2021 so that the analyzed data is indeed updated. After reviewing the discussion, we can summarize the findings of published evidence stating that human resource management in the business world in the modern era requires technological power to work there truly compete because HR management is closely related to superior policies and practices businesses need. Thus this simple finding becomes an impactful input for researchers, university instructors, and another world of business practice.